Evaluation of insulin resistance in overweight and obese dogs - Julio R Ramos S; Víctor Castillo (International Journal of Veterinary Science and Research - Peertechz Publications, 2020)
Prevalence of obesity in dogs has been increasing in the last decade, being the most common form of malnutrition and consequently has increased the appearance of metabolic diseases in this species. The objective of this study is to compare biochemical and endocrine profiles related to insulin resistance between lean and obese canine patients and to find similarities with the human metabolic syndrome. A total of 20 dogs were divided into two groups (lean and obese) of 10 dogs each, evaluating body mass index, HOMA-IR, HOMA-B, insulin, glucose, cholesterol, triglycerides, HDLc, LDLc, cortisol, T4total and freeT4. The results showed significant increase in BMI, HOMA-IR, insulin, glucose, cholesterol, HDLc, triglycerides and cortisol in obese patients, similar to metabolic syndrome described in humans.